2022
DOI: 10.7759/cureus.32034
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the 10-Year Risk of Developing Type 2 Diabetes Among Saudi Adults Based on the Finnish Diabetes Risk Score

Abstract: Background and objective Diabetes mellitus (DM) is a chronic, metabolic disease characterized by elevated blood glucose levels that eventually lead to several acute and chronic complications. Type 2 DM (T2DM) is a major healthcare problem globally as well as in the Kingdom of Saudi Arabia (KSA). Predicting and identifying people at high risk for developing T2DM will help implement preventive measures for these individuals. In light of this, the present study was designed to estimate the 10-year risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…жителей ≥18 лет, показало, что 35% обследованных относились к группе риска развития СД2 [1346]. В представительной выборке Королевства Саудовская Аравия средний балл по шкале FINDRISC составил 7,53 балла, а каждый пятый обследованный имел риск развития СД2 умеренный и выше [1347].…”
Section: предиабет сахарный диабет и коморбидность 421 предиабет и ко...unclassified
“…жителей ≥18 лет, показало, что 35% обследованных относились к группе риска развития СД2 [1346]. В представительной выборке Королевства Саудовская Аравия средний балл по шкале FINDRISC составил 7,53 балла, а каждый пятый обследованный имел риск развития СД2 умеренный и выше [1347].…”
Section: предиабет сахарный диабет и коморбидность 421 предиабет и ко...unclassified
“…A recent study found that the general Saudi population has a moderate to high risk of acquiring T2DM, which amounts to about 18% of the population. [10] Possible explanations for the high prevalence in these nations include the adult population's notable occurrence of obesity and other non-communicable disease risk factors, particularly in Saudi Arabia, which is second. [11] A recent study estimated the prevalence of T2DM in the Middle-East, including in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%